Random Lasing Behaviour in Al-doped Zno Nanorods - Atiqah Nabieha Azmi; Wan Maryam Wan Ahmad Kamil; Haslan Abu Hassan; Otto L. Muskens; Wan Zakiah Wan Ismail (Elsevier, 2024)
Indexed by WOS/Scopus/ERA